Reuse and Recycling of Livestock and Municipal Wastewater in Chilean Agriculture: A Preliminary Assessment - Villamar-Ayala, C (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Chile is an agricultural power, but also one of the most vulnerable countries to climate change and water shortage. About 50% of the irrigated agriculture land in Chile is in the central zone, thanks to its agricultural-climatic characteristics that provide an adequate water supply (100-4000 m3/s). However, the vulnerability scenario in this zone is high due to the seasonal availability of water resources. Therefore, opportunities to use non-conventional alternative sources (e.g., wastewater) become an appealing and feasible option due to the high population and animal density (> 76%) in this part of the country. Moreover, the physicochemical characteristics of the municipal and livestock wastewater suggest that there are potential opportunities to recycle nutrients for agricultural production. In Chile, wastewater reuse opportunities are noted by the wide coverage of wastewater treatment programs, with municipal and intensified livestock production taking up most of the percentage (> 99%). Nevertheless, more than 70% of wastewater treatment systems reach biological secondary treatment, which suggests reuse possibilities only for non-food crops. Therefore, this paper is focused on a preliminary analysis of the potential of reusing and recycling municipal and livestock wastewater for Chilean agriculture. There is some reuse work occurring in Chile, specifically in the use of municipal and livestock wastewater for cereal crops (animal feed), forests, and grasslands. However, aspects related to the long-term effects of these practices have not yet been evaluated. Therefore, municipal and livestock wastewater in Chile could be re-valued in agriculture, but the current quality and condition of treated wastewater do not ensure its safe use in food crops. In addition, state policies are needed to provide sustainability (circular and ethic economy) to water reusing/recycling in agriculture. © 2018 by the authors.